PHYSICOCHEMICAL CHARACTERIZATIONS OF PHAGE LYTIC TO STAPHYLOCOCCUS AUREUS FROM MASTITIS, SEWAGE WATER AND FARM YARD SLURRY OF LIVESTOCK - R. Durairajan; M.S.Murugan; K. Kanagaraj Durai (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was performed to isolate and characterize the lytic phage Staphylococcus aureus, from the farm yard resource of Cattle, Buffaloe and Poultry in all 50 samples were obtained and 2 phages were recovered. They were characterized on the basis of plaque morphology, host range determination, effect of pH and temperature on phages against Staphylococcus aureus,. This preliminary study could be useful to search potential candidate phage for treatment and control of Bovine mastitis.